Pengaruh Disiplin Kerja, Beban Kerja dan Dukungan Organisasi Terhadap Kinerja di Perusahaan Daerah Air Minum (PDAM) Delta Tirta Sidoarjo - Putri, Indri Wahyuni Kusuma; Firdaus, Vera; Abadiyah, Rifdah (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The success of a company is influenced by many factors including natural resources, capital, technology and available human resources. Employees who want to improve their performance must show discipline. Workload greatly affects employee performance at work. Some of the impacts that may occur in organizations are due to workloads that are too high or too low. This situation can lead to less efficiency in the performance of tasks. In addition, it is important to strive to create a positive work environment. Organizational support is a very crucial factor for employees in an organization. The presence of such support in the organization can make a positive contribution, encouraging employees to actively strive to achieve organizational goals. This study aims to analyze the effect of work discipline, workload and organizational support on performance. Research using quantitative methods descriptive research type. Sampling in this study were 120 respondents with purposive sampling method. This study uses data collection techniques through questionnaire distribution, and data analysis methods using SPSS statistical tools. The results showed that Work Discipline, Workload, and Organizational Support have a significant influence on employee performance at PDAM Delta Tirta Sidoarjo.